Review of sonic boom prediction and reduction methods for next generation of supersonic aircraft - Bonavolontà, Giordana; Lawson, Craig P.; Riaz, Atif (MDPI, 2023)
The reduction of sonic boom levels is the main challenge but also the key factor to start a new era of supersonic commercial flights. Since 1970, a FAA regulation has banned supersonic flights overland for unacceptable sonic booms at the ground, and many research studies have been carried out from that date to understand sonic boom generation, propagation and effects, both on the environment and communities. Minimization techniques have also been developed with the attempt to reduce sonic boom annoyance to acceptable levels. In the last 20 years, the advances in both knowledge and technologies, and companies and institutions’ significant investments have again raised the interest in the development of new methods and tools for the design of low boom supersonic aircraft. The exploration of unconventional configurations and exotic solutions and systems seems to be needed to effectively reduce sonic boom and allow supersonic flight everywhere. This review provides a description of all aspects of the sonic boom phenomenon related to the design of the next generation of supersonic aircraft. In particular, a critical review of the prediction and minimization methods found in the literature, aimed at identifying their strengths, limitations and gaps, is made, along with a complete overview of disruptive unconventional aircraft configurations and exotic active/passive solutions to boom level reduction. The aim of the work is to give a clear statement of state-of-the-art sonic boom prediction methods and possible reduction solutions to be explored for the design of next low-boom supersonic aircraft.
Keywords: supersonic aircraft design; sonic boom modeling and prediction; aerodynamics; acoustics